The Impending Global Challenge of Antimicrobial Resistance: A Call for Urgent Action - Giri, Purushottam; Aikat, Aditi (Indian Journal of Community Health, 2024)
Antimicrobial resistance (AMR) is a critical global health issue driven by antibiotic misuse and overuse in various sectors, leading to the emergence of resistant microorganisms and represents an impending pandemic. Against the backdrop of COVID-19 pandemic, conflicts, and the escalating impact of anthropogenic climate change, the emergence and rapid escalation of antimicrobial resistance (AMR) represent one of the most significant and imminent global public health threats of the 21st century.(1) As bacteria, viruses, fungi, and parasites increasingly evolve resistance to drugs that once treated infections effectively, the ‘superbugs’ such as Methicillin-resistant Staphylococcus aureus (MRSA) and extremely drug-resistant tuberculosis, bacteria that are difficult to treat have emerged. This has brought humanity to the brink of a post-antibiotic era, where re-emergence of common infections is being noted. With resistance on the rise, surgical procedures like organ transplants and cesarean sections, cancer treatments where antibiotics are crucial, and management of life-threatening infectious diseases such as pneumonia, TB, HIV, and malaria are at risk of becoming dangerous due to the high potential for untreatable infections. (2)